Structural characterization of recombinant bovine Go alpha by spectroscopy and homology modeling - (:unkn) unknown (IOS PRESS, 2011)
Go, a member of heterotrimeric guanine nucleotide-binding proteins, is the most abundant form of G protein in the central and peripheral nervous systems. Go alpha has a significant role in neuronal development and function but its signal transduction mechanism remains to be clarified. In this study, the bovine Go alpha subunit was overexpressed and purified into homogeneity. Its activity was studied using [S-35] GTP gamma S binding, intrinsic fluorescence and BODIPY assays. The secondary structure was determined by both FTIR and CD spectroscopy as 42.3% alpha-helix, 13.4% beta-sheet and 24.3% beta-turn. A theoretical structure model was constructed. The structure from homology modeling is in very good agreement with the crystal structure of mouse Go alpha subunit except for the loop between alpha B-alpha C helices. This model was docked to the mouse RGS16 molecule. T117 on the alpha B-alpha C loop of Go alpha interacted with K172 on RGS16 as opposed to the T117 and K164 interaction in mouse.
Keywords: Go alpha protein; FTIR spectroscopy; circular dichroism; homology modeling; PROTEIN SECONDARY STRUCTURE; CIRCULAR-DICHROISM; NUCLEOTIDE-BINDING; INFRARED-SPECTRA; FLUORESCENCE; MEMBRANES; SUBUNIT; HADDOCK